Dreamweaver MX/Fireworks MX - Crumlish, Christian (Sybex, 2002)
Dreamweaver MX / Fireworks MX Savvy is a thorough, in-depth resource for every user of Macromedia's powerful web publishing tools. Heading up a team of experienced Web professionals, best-selling author Christian Crumlish teaches you everything from best-practices methodology to the nitty gritty of such common tasks as: migrating sites to Dreamweaver, optimizing images for Web use, creating dynamic content, building web applications, administering your site, and more.